Ciclagem de nutrientes, produção de milho em sistema de integração lavoura-pecuária subsequente ao consórcio de pastagens hibernais - Ghizzi, Lucas Ghedin (2015)
The Integrated Crop-Livestock Systems is focuses on the pursuit of excellence in production, being recognized as an tool of optimization natural and financial resources , combining the interaction between interfaces soil , plant and animal. The objective of this study was to evaluate the effect of inclusion of vetch as winterly herbage, with grazing animals receiving or not supplementation, in the production of subsequent crop (maize production for silage and grain yield ) in the dynamics of decomposition and nutrient release post grazing residual biomass and manure, on a crop-livestock system. The work was developed in Federal Technological University of Paraná - Campus Dois Vizinhos ( UTFPR -DV) and the consortium of forage species, were: oat + ryegrass + supplementation; oat + ryegrass + vetch and oat + ryegrass + vetch + supplementation, all with and without grazing. It was used ground maize sieve of 1 mm as supplementation. Were evaluated the decomposition of MS and release of nutrients (nitrogen, phosphorus and potassium) of biomass consortium herbage and manure, corn yield components (number of rows in each ear, number of kernels per row, grains per ear, mass of thousand grain) grain yield (kg ha-1) and production of silage from whole plant. Among the studied nutrients, nitrogen was the more returned to the system after the decomposition of biomass grazed, for not grazed and originating from cattle manure. The biomass decomposition rate was influenced by grazing, with faster decay, whereas for faecal dry matter, the decomposition rate was higher for manure from animals that were supplemented, not observing the effect of vetch return nutrients to the soil. The presence of the animal influenced only mass thousand corn grains, which proved to be superior in ungrazed areas.